Social Impact Assessment di Malaysia dan New South Wales, Australia: Pembelajaran bagi Pengaturan di Indonesia pada Masa Mendatang (Social Impact Assessment in Malaysia and New South Wales, Australia: Lessons for Future Regulation in Indonesia) - Dewi, Anggita Mustika; Ginting, Albert Suprayogi; Aina, Destriananda Safa (Universitas Islam Indonesia, 2026)
The legal framework for land acquisition in Indonesia has not systematically integrated Social Impact Assessment (SIA), thus, protection against the social impacts of development has not been optimally implemented. Unlike Indonesia, which is still developing SIA regulations, Malaysia and New South Wales, Australia have implemented SIA in the land acquisition process for development. This research aims to analyze SIA regulations in these two jurisdictions and identify relevant norms for strengthening SIA regulations in Indonesia. This research is a normative legal study using a statute approach and a comparative approach. The collected data were analyzed qualitatively. The research findings indicate that strengthening SIA regulations in Indonesia requires a legal basis at the statutory level, making amendments to Law Number 2 of 2012 urgently necessary. These regulations also need to be supplemented with implementing regulations, such as Ministerial Regulations and SIA Guidelines, to further regulate the technical provisions for SIA implementation. These include the classification of projects that require SIA based on their social risk level, the implementation of SIA from the land acquisition planning stage, information provision mechanisms that combine public displays and digital platforms, diverse, inclusive, and meaningful public participation, and proportional, efficient, and risk-based monitoring and evaluation mechanisms. These findings provide a normative basis for developing SIA regulations to strengthen the protection of the rights of affected communities, particularly vulnerable groups and indigenous communities, in realizing more responsive, participatory, inclusive, and equitable land acquisition.